Alternatives to universities in higher education : country study. The United States - (:unkn) unknown (My University, 1989)
The paper discusses the non-university sector of postsecondary education in the United States, its relationship to the traditional university and college sector, and its role in education and training in America. The authors have defined the non-university sector as including both the two-year community, technical and junior colleges ordinarily considered part of American higher education and the "third sector", which includes other post- secondary technical and vocational schools (many of which are profit-making) and courses offered by corporations and the military services. The focus is primarily on community colleges, which now enroll over 40 percent of all students in postsecondary education in the United States. For those unfamiliar with American postsecondary a brief description of the system and a note on American terminology as an appendix to this paperis included. (IAB2) In dem Papier werden der nichtuniversitäre Bereich der postsekundären Ausbildung in den USA, seine Beziehungen zum traditionelen Universitäts- und Collegebereich und seine Rolle im Bildungs- und Ausbildungsbereich generell diskutiert. Der Anhang enthält eine kurze Beschreibung des US-amerikanischen postsekundären Bildungssystems und einige Bemerkungen zur Terminologie. (IAB2)
Alternativen zu den Universitäten in der Hochschulbildung. Länderstudie USA
Keywords: G 2.3.5 Wirtschaftsstrukturwandel; Struktur; Berufsbildendes Schulwesen; Absolvent; Arbeitsmarktchance; Quantitative Angaben